2021
DOI: 10.21873/anticanres.15251
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pre-radiotherapy Sleep Disorders in Patients With Rectal or Anal Cancer

Abstract: Background/Aim: Radiotherapy and radiochemotherapy are common treatments for rectal and anal cancer. Anticipation of treatment may cause distress and sleep disorders. This study aimed to identify risk factors for sleep disorders. Patients and Methods: In 42 patients with rectal or anal cancer scheduled for radiotherapy, 16 characteristics were analyzed for associations with pre-radiotherapy sleep disorders including age, gender, performance score, comorbidity, patient's or family history of additional cancer/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
3
11
1
Order By: Relevance
“…However, the prevalence of sleep problems was not stated. In the present small study, the prevalence of sleep disorders prior to planned radiochemotherapy was 50.0%, which was higher than that prior to radiotherapy or radiochemotherapy for other malignancies such as gynecological cancers, prostate cancer, rectal cancer, lung cancer, and anal cancer (19)(20)(21)(22)(23).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…However, the prevalence of sleep problems was not stated. In the present small study, the prevalence of sleep disorders prior to planned radiochemotherapy was 50.0%, which was higher than that prior to radiotherapy or radiochemotherapy for other malignancies such as gynecological cancers, prostate cancer, rectal cancer, lung cancer, and anal cancer (19)(20)(21)(22)(23).…”
Section: Discussioncontrasting
confidence: 62%
“…In a previous study of 62 patients with gynecological cancers, pre-radiotherapy sleep disturbances were significantly associated with greater numbers of physical problems, and a trend was found for greater numbers of emotional problems (19). Moreover, in a study of 42 patients with rectal or anal cancers, preradiotherapy sleep disturbances showed significant associations with higher distress scores and with greater numbers of physical problems or emotional problems (20). In a study of 48 patients scheduled for radiotherapy of prostate cancer, higher distress scores and greater numbers of physical problems were significantly associated with pre-radiotherapy sleep disturbances (21).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Associations between higher distress scores and sleep problems prior to radiotherapy or radiochemotherapy were shown for patients with breast cancer, prostate cancer, and rectal or anal cancer (20,22,27). A trend for an association between pre-radiotherapy sleep problems and female gender was also reported for patients irradiated for rectal or anal cancer (27). However, since our present study can be considered unique, as it is the first study evaluating sleep problems prior to radiochemotherapy in patients with malignant gliomas, its results may not be directly compared to studies that included differing tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the study investigating insomnia in patients with recurrent glial neoplasms, trends were observed for an association between insomnia and fatigue (physical problem) (11). Associations between higher distress scores and sleep problems prior to radiotherapy or radiochemotherapy were shown for patients with breast cancer, prostate cancer, and rectal or anal cancer (20,22,27). A trend for an association between pre-radiotherapy sleep problems and female gender was also reported for patients irradiated for rectal or anal cancer (27).…”
Section: Discussionmentioning
confidence: 99%